Modeling the Action Potential in Characeae Nitellopsis obtusa: Effect of Saline Stress - Kisnieriene, Vilma; Lapeikaite, Indre; Pupkis, Vilmantas; Beilby, Mary Jane (Frontiers in Plant Science, 2019)
Action potentials (AP) of characean cells were the first electrical transients identified in plants. APs provide information about plethora of environmental cues. Salinity stress is critical for plants and impacts on excitability. The AP of brackish Characeae Nitellopsis obtusa, obtained in artificial pond water (APW) and under osmotic stress of 90 or 180 mM sorbitol APW or saline stress of 50 or 100 mM NaCl APW, were simulated by the Thiel-Beilby model (Beilby and Al Khazaaly, 2016, AIMS Biophysics 3: 431; 2017 AIMS Biophysics 4: 298). The model is based on a paradigm from animal systems, featuring the second messenger inositol 1,4,5-triphosphate (IP3) mediating the opening of Ca2+ channels on internal stores. In plants the IP3 receptors have not been identified, so other second messengers might translate the threshold plasma membrane depolarization to Ca2+ release. The increased Ca2+ concentration in the cytoplasm activates Cl- channels, which lead to the depolarizing phase of the AP. The repolarization to normal resting potential difference (PD) results from the Ca2+ being re-sequestered by the Ca2+ pumps, the closure of the Cl- channels, efflux of K+ through the depolarization-activated outward rectifier channels and the continuing activity of the proton pump. The Nitellopsis AP form is longer in APW compared to that of Chara, with more gradual repolarization. The tonoplast component of the AP is larger than that in Chara australis. The plasma membrane AP is prolonged by the exposure to saline to a “rectangular” shape, similar to that in Chara. However, the changes are more gradual, allowing more insight into the mechanism of the process. It is possible that the cells recover the original AP form after prolonged exposure to brackish conditions. Some cells experience tonoplast APs only. As in Chara, the proton pump is transiently inhibited by the high cytoplasmic Ca2+ and gradually declines in saline media. However, if the cells are very hyperpolarized at the start of the experiment, the pump inhibition both by the AP and by the saline medium is mitigated. The model parameters and their changes with salinity are comparable to those in Chara.